Evaluation protects research investments - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Investing in research is a long-term and risky proposition , according to one of the ten papers in this collection. Dedicated to agricultural research in developing countries, it provides one of the most up-to-date overviews of the art, and...